Desain Formulir Posyandu Lansia Desa Congkrang Kecamatan Muntilan Kabupaten Magelang Jawa Tengah - Kuswanto Hardjo; Eniyati; Kori Puspita Ningsih (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Recording and Reporting are parts of the Medical Record. According to Law No. 29 of 2004 on The Practice of Medicine, Medical Record is a file containing records and documents about the patient's identity, examination, treatment, actions, and other services given to the patient. Good data collection tools can produce accurate and valuable health information. Posyandu elderly Congkrang Village Muntilan District Magelang has been done regularly, but there is no good documentation of examination results. Documentation is written in books, but Posyandu participants can not access it. Forms have not available yet, so participants can not monitor the results of their examinations. The purpose of this study is the creation of health record forms and health examinations documentation of the elderly on an ongoing basis. This research is a development research or Research and Development (R&D) with a qualitative approach. The study results in health record forms in Posyandu elderly